PRUDENT BANKING PRINCIPLE DALAM MENYALURKAN KREDIT KEPADA USAHA MIKRO, KECIL, MENENGAH DAN KOPERASI (UMKM-K) DARI SISI PERATURAN PERBANKAN DI INDONESIA - Widita Kurniasari (Trunojoyo University of Madura, 2011)
Prudent banking principle is a principle which states that the bank in carrying out its functions and activities must be careful (prudent) in order to protect the public funds entrusted to him. Condition of Micro, Small and Medium-Cooperatives in general terms of the availability and condition of collateral held is not adequate, and recording / documentation is relatively limited. At the same time the ability of commercial banks with valuation techniques that have led to a relatively limited public banks have difficulty in assessing the business prospects of Micro, Small and Medium-Cooperative and in turn the ability to pay Micro, Small and Medium-Cooperative. The implications of these conditions lead to commercial banks should provide substantial reserve fund if it will extend credit to Micro, Small and Medium-cooperative and that means it will reduce the ability of banks to meet the required CAR of Bank Indonesia. Finally, banks will choose to allocate funds raised to a safer destination, such as SBI does not require a reserve fund.